Tuning of the Optical Properties of the Transparent Conducting Oxide SrVO3 by Electronic Correlations. Issue 7 (25th January 2019) - Boileau, Alexis; Cheikh, Aïmane; Fouchet, Arnaud; David, Adrian; Labbé, Christophe; Marie, Philippe; Gourbilleau, Fabrice; Lüders, Ulrike
Abstract: The vanadate SrVO3 is a transparent conductor perovskite with optical and electrical properties competing with those of the most‐used indium tin oxide material. Although its charge density is comparable to that of metals, SrVO3 shows a plasma frequency below the visible range due to strong electronic correlations characterizing the electronic transport in this material and enhancing the effective mass. Therefore, the well‐known interplay between the structure and the electronic properties of strongly correlated systems can be used in such transparent conductor to tune the optical properties, as the plasma frequency also depends on the effective mass. In this study, SrVO3 films are grown by pulsed laser deposition onto different lattice mismatched perovskite substrates such as SrTiO3, LaAlO3, and (LaAlO3 )0.3 (Sr2 TaAlO6 )0.7 at different growth temperatures. The structural, electronic, and optical properties are analyzed, illustrating the influence of the strain on the structure of the films and on a shift of the plasma frequency. The electronic correlations in this new group of transparent conducting oxides can be therefore used as a supplementary lever for the tuning of the functional properties. Abstract : SrVO3 thins films are grown by pulsed laser deposition onto SrTiO3, LaAlO3, and (LaAlO3 )0.3 (Sr2 TaAlO6 )0.7 . Both optical and electrical properties of the films are investigated and demonstrate that such strongly correlated system is competing with the indium tin oxide as new transparent conducting oxide. The plasma frequency of the films depends on the substrate and can be easily tuned toward the infrared region.